Literacy of Lower Classes Students Primary School in the 2013 Curriculum during the Pandemic COVID-19 - Azizatul Khairi; Rambat Nur Sasongko; Muhammad Kristiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the application of reading literacy in the 2013 Curriculum for the COVID-19 pandemic era. This study uses a descriptive content analysis study and literature studies. The findings showed that educators carried out various activities to implement students' reading literacy through blended learning activities, both at school and home. In conclusion, teachers monitor the increase in reading literacy through assignments performed by students in learning from home. Then, teachers and student guardians work together in online learning to improve students' reading literacy. Keywords: COVID-19, Curriculum 2013, Literacy, Lower Class, Primary School